Quantitative analysis of miroestrol and kwakhurin for standardisation of thai miracle herb 'kwao keur' (pueraria mirifica) and establishment of simple isolation procedure for highly estrogenic miroestrol and deoxymiroestroly - Satoko Shimokawa (2018)
Quantitative analysis of miroestrol (1) and kwakhurin (3) by HPLC, leading to standardisation of commercially available Thai miracle herb 'Kwao Keur' which has been identified with Pueraria mirifica, was established using independent solvent systems. The simple isolation procedure of highly estrogenic miroestrol (1) and deoxymiroestrol (2) from P. mirifica was also proposed. © 2013 Taylor and Francis.